PEER ASSESSMENT FOR IMPROVING WRITING DESCRIPTIVE TEXT OF THE TENTH GRADERS OF SENIOR HIGH SCHOOL SETIA BUDHI SEMARANG - Wiwik Yully Widyawati (ETERNAL (English Teaching Journal), 2016)
The problems of the study  can be formulated as follows (1) How effective is peer assessment technique applied to students with low and high grammar ability in writing descriptive text?, (2) How effective is teacher assessment technique applied to students with high and low grammar ability in writing descriptive text, (3) Is there any significant interaction among grammar ability, peer assessment technique and writing ability. The research design employed in this study was Experimental Design (factorial design) consisting of a pre test, and post test for control group design and Experiment group. This research involved three variables which consisted of dependent variable (writing ability), independent variable (Peer Assessment Technique) and Grammar ability as moderator. This study found that peer assessment technique can be used to give practice in writing as well as in conducting this technique for teaching writing because it had given effect to the student writing descriptive text. It can be proven from the students’ score. Through this technique, the students could develop and improve their skill either in writing, grammar or vocabulary. They also became responsible to asses their friend’s work and increased their motivation. So, this technique of peer assessment should be used to improve English writing and grammar skill and an English teacher must improve his knowledge in English teaching method so the goal of teaching is gained.